2018
DOI: 10.1007/978-3-662-58387-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization in Bitcoin and Ethereum Networks

Abstract: Blockchain-based cryptocurrencies have demonstrated how to securely implement traditionally centralized systems, such as currencies, in a decentralized fashion. However, there have been few measurement studies on the level of decentralization they achieve in practice. We present a measurement study on various decentralization metrics of two of the leading cryptocurrencies with the largest market capitalization and user base, Bitcoin and Ethereum. We investigate the extent of decentralization by measuring the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(140 citation statements)
references
References 32 publications
2
118
0
Order By: Relevance
“…Even though people design systems for good decentralization, in practice, we often observe that blockchain systems are highly centralized. Bitcoin and Ethereum, as representative examples, are already well known to be highly centralized in terms of network and mining [4], [14]- [16]. Currently, most of the computational power (or mining power) in these systems is concentrated in only a few nodes, called mining pool, 1 where individual miners gather together for mining.…”
Section: B Decentralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though people design systems for good decentralization, in practice, we often observe that blockchain systems are highly centralized. Bitcoin and Ethereum, as representative examples, are already well known to be highly centralized in terms of network and mining [4], [14]- [16]. Currently, most of the computational power (or mining power) in these systems is concentrated in only a few nodes, called mining pool, 1 where individual miners gather together for mining.…”
Section: B Decentralizationmentioning
confidence: 99%
“…This spurs the desire to achieve a fully decentralized system. Even though many discussions and attempts have been made to achieve good decentralization, existing systems, except for Bitcoin, Ethereum and Stellar, have rarely been analyzed [4], [21]. In this paper, for the first time, we not only study the possibility of full decentralization but also extensively investigate the existing coins.…”
Section: B Decentralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been studied analytically and with the help of simulations [6,7]. In [15], the degree of centralization of Bitcoin and Ethereum is investigated. The authors found both networks to be highly centralized in terms of (geographical) mining power distribution.…”
Section: Related Workmentioning
confidence: 99%
“…The blockchain has an underlying peerto-peer protocol, in charge of disseminating information on novel blocks being produced, to be added to the blockchain, or novel transactions that might be inserted into novel blocks. A flooding mechanism is often used to disseminate information, while the peer-to-peer overlay is built using some peer discovery mechanism [14]. For instance, a random selection protocol is used in Bitcoin, while Ethereum employs a UDP-based node discovery mechanism inspired by Kademlia [16].…”
Section: Introductionmentioning
confidence: 99%